Significant linkage to chromosome 12q24.32–q24.33 and identification of SFRS8 as a possible asthma susceptibility gene - Brasch‐Andersen, C (BMJ Group, 2006)
BACKGROUND: Asthma is a complex genetic disorder. Many studies have suggested that chromosome 12q harbours a susceptibility gene for asthma and atopy. Linkage on chromosome 12q24.21–q24.33 was investigated in 167 Danish families with asthma. METHODS: A two step procedure was used: (1) a genome‐wide scan in one set of families followed by (2) fine scale mapping in an independent set of families in candidate regions with a maximum likelihood score (MLS) of ⩾1.5 in the genome‐wide scan. Polymorphisms in a candidate gene in the region on 12q24.33 were tested for association with asthma in a family based transmission disequilibrium test. RESULTS: An MLS of 3.27 was obtained at 12q24.33. The significance of this result was tested by simulation, resulting in a significant empirical genome‐wide p value of 0.018. To our Knowledge, this is the first significant evidence for linkage on chromosome 12q, and suggests a candidate region distal to most previously reported regions. Three single nucleotide polymorphisms in splicing factor, arginine/serine‐rich 8 (SFRS8) had an association with asthma (p⩽0.0020–0.050) in a sample of 136 asthmatic sib pairs. SFRS8 regulates the splicing of CD45, a protein which, through alternative splice variants, has an essential role in activating T cells. T cells are involved in the pathogenesis of atopic diseases such as asthma, so SFRS8 is a very interesting candidate gene in the region. CONCLUSIONS: Linkage and simulation studies show that the very distal part of chromosome 12q contains a gene that increases the susceptibility to asthma. SFRS8 could act as a weak predisposing gene for asthma in our sample.